Influence of the steel disk on the NVH behavior of industrial wet disk clutches - Strobl, Patrick; Völkel, Katharina; Schneider, Thomas; Stahl, Karsten (Industrial Lubrication and Tribology, 2025)
Purpose: Industrial drivetrains use wet disk clutches for safe and reliable shifting. Advances over the past decades regarding the formulation of lubricants and the composition of friction materials have led to reliable clutch systems. In this context, the friction behavior is crucial for the correct operation of the clutch. Nevertheless, the friction behavior and its influencing factors are still the object of modern research. The purpose of this study is to investigate how the choice of the steel disk influences the noise vibration and harshness (NVH) behavior of wet industrial clutches. Design/methodology/approach: To investigate the influence of the steel disk on the friction and NVH behavior of industrial wet disk clutches, experimental investigations with relevant friction systems are conducted. These tests are performed at two optimized test rigs, guaranteeing transferable insights. The surface topography of the steel disk and the friction lining are measured for one friction system to identify possible relations between the surface topography and the friction behavior. Findings: The steel disk can influence the friction behavior of wet disk clutches. Using a different steel disk surface finish, corresponding results can show differences in the shudder tendency, leading to a nonfavorable NVH behavior – different gradients of the coefficient of friction over sliding velocity cause this phenomenon. Originality/value: This work gives novel insights into the friction and NVH behavior of industrial wet disk clutches. It supports engineers in the optimization of modern friction systems. Peer review: The peer review history for this article is available at: https://publons.com/publon/10.1108/ILT-02-2024-0054/
CRIS-Team Scopus Importer:2025-05-19
Keywords: Boundary friction; NVH behavior; Sinter friction lining; Steel disk; Surface topography; Wet clutch